2011
DOI: 10.1007/s11814-011-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrous iron oxide for removal of inorganic contaminants in simulated stormwater: A batch sorption kinetics study

Abstract: Urban stormwater runoff, which consists of inorganic and organic contaminants, is a major source of pollutants to receiving waters and therefore they need to be removed. Simultaneous removal of contaminants, Cd 2+ , Cu 2+ , Ni 2+ , Zn 2+ (heavy metal cations), and SeO 4 2− (oxyanion) from a simulated stormwater by a hydrous ferric oxide (HFO) was studied in batch and column sorption experiments. In the batch experiment the rate of sorption of the ions was rapid at the beginning and reached equilibrium in appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Iron oxide nanoparticles used for MRI imaging have also been observed to undergo enhanced cellular uptake, [84][85][86][87][88][89] and a similar TfR mediated mechanism may be operative. It has also been observed that toxic heavy metals in aquatic environments adsorb to hydrated ferric oxide, 90,91 and this behavior is viewed as a potential method for removing toxic metals from the environment. [92][93][94][95][96][97][98] In the context of surface iron(III) providing a mechanism for endocytosis, the TfR mediated uptake of ferric oxide nanoparticles may need to be considered in assessing the bioavailability of heavy metals adsorbed on such iron oxide particles.…”
Section: Discussionmentioning
confidence: 99%
“…Iron oxide nanoparticles used for MRI imaging have also been observed to undergo enhanced cellular uptake, [84][85][86][87][88][89] and a similar TfR mediated mechanism may be operative. It has also been observed that toxic heavy metals in aquatic environments adsorb to hydrated ferric oxide, 90,91 and this behavior is viewed as a potential method for removing toxic metals from the environment. [92][93][94][95][96][97][98] In the context of surface iron(III) providing a mechanism for endocytosis, the TfR mediated uptake of ferric oxide nanoparticles may need to be considered in assessing the bioavailability of heavy metals adsorbed on such iron oxide particles.…”
Section: Discussionmentioning
confidence: 99%